Toll-Like Receptors and Inflammation in the CNS - Joong Lee, S.; Lee, S. (Current Drug Targets - Inflammation & Allergy, 2002)
The innate immune system recognizes “non-self” by employing a set of germline-encoded receptors called Toll-like receptors (TLRs), originally characterized in Drosophila. TLRs are involved in the recognition of various microbial-derived molecules, including lipopolysaccharide (LPS), lipoteichoic acid (LTA), and peptidoglycan (PGN), as well as unmethylated bacterial DNA. The TLR-mediated intracellular signaling pathways converge to activate nuclear factor-kappa B (NF-κB) and c-Jun N-terminal kinases (JNKs), which induce the transcription of a series of cytokine / chemokine genes that are involved in the initiation or regulation of the inflammatory response. It is now known that, like other peripheral organs, the central nervous system (CNS) is also under constitutive immune surveillance by CNS-resident glial cells (microglia and astrocytes) and CNSinfiltrating immune cells. The recent progress in our understanding of TLR functions in the innate immune response sheds new light on how inflammatory immune responses are initiated within the CNS. In this review, we discuss recent studies on TLRs and their ligands, signal transduction pathways activated by TLRs, and the mechanisms through which these various activation events occur. Finally, we discuss how TLRs might play similar important roles in CNS inflammation.
Keywords: tlr